Knowledge, attitude and practices of mothers regarding immunization - Ali, Shoaib; Ifat, Mubina; Amin, Javeria; Jamil, Samia; Aaraj, Sahira; Naeem, Hamza; Javed, Saba; Nazir Siddiqui, Shahida; Saeed Khokhar, Hamza; Zahoor, Sarmad (International Journal of Medicine, 2022)
Introduction: Immunization strengthens the defense mechanism of the body and offers protection against potential diseases. The rate of immunization is one of the best measures of public health management and quality. To increase the rate of immunization, parental decisions about vaccinations are very necessary. Parents' knowledge and attitude towards immunization influence the prevalence of infectious diseases. Moreover, vaccination is considered one of the most cost-effective public health tools to prevent infectious diseases.Objective: The objective of this study is to assess the frequency of adequate knowledge, positive attitude and good practices of mothers regarding immunization.Materials and Methods: It was a cross-sectional study which was conducted in The Children's Hospital & Child Health Institute, Lahore. A total of 125 children who met the selection criteria were enrolled. Parents were then questioned and validated by vaccination card status regarding various Expanded Immunization Policy (EPI) vaccinations and complete previous records. The awareness and attitude of mothers regarding vaccination was also considered that either they were aware of the vaccination status or not. All the data was collected and reported in the form of a questionnaire.Results: In this study93 mothers had a good understanding, 77 mothers had a good practice, and 66 mothers had a positive attitude towards immunization. Childs’ gender, mothers’ educational status, socio-economic status, good practice, and positive attitude had no significant impact on adequate knowledge about vaccination.Conclusion: It was concluded from this study that mothers’ knowledge about immunization was adequate, however good practice and positive attitude were not up to the mark.